Pengembangan Model Pembelajaran Berbasis Pendidikan Karakter Untuk Meningkatkan Kemandirian Sosial Anak Usia Dini - Titi Chandrawati; Mukti Amini; Siti Aisyah; Yaswinda Yaswinda (Atthiflah: Journal of Early Childhood Islamic Education, 2026)
This study aims to develop a character education-based learning model to improve early childhood social independence. Using the Research and Development (R&D) method of Borg & Gall (2007), the research was conducted over two years. The first year produced prototype models in the form of manuals, RPPH, songs, bigbooks, and gameboards. In the second year, a limited trial was held in Tangerang and field trials were held in Tangerang, Sawangan, Jakarta, and Padang. The results of the study show that this learning model is effective in increasing five character values: honesty, toughness, intelligence, caring, and social independence. The teacher's assessment of the model is in the score range of 3–4 from a scale of 4, including the good to excellent category. Major revisions include simplifying the gameboard into a traditional game, revising the lyrics of the song "Aku", and adding a new bigbook. This model is recommended for use in early childhood education institutions in Indonesia